Length variation of chloroplast simple sequence repeats in the genus Eucalyptus L’Hér. - Kumar, Sonu; Shanker, Asheesh (Plant Science Today, 2020)
Eucalyptus L'Hér. is an economically important genus of plants with several environmental significances and great industrial advantages. To accelerate breeding and conservation studies, efforts on molecular breeding and molecular genetic analysis are underway in the genus Eucalyptus. Despite these efforts, no sufficient information is available about common, polymorphic and unique chloroplast simple sequence repeats (cpSSRs) in the genus Eucalyptus. . These repeats consist of 1-6 nucleotides and play important role in the development of molecular markers, genetic mapping and plant breeding. In the present study, a total of 920 cpSSRs were detected and length variation of cpSSRs analysed between each pair of species among 31 chloroplast genome sequences of the genus Eucalyptus. Additionally, cross species transferability of common and polymorphic cpSSRs were also observed. The common, unique and putative polymorphic cpSSRs analysed in this study can be used for species identification and genetic diversity studies of Eucalyptus.